2020
DOI: 10.2196/14337
|View full text |Cite
|
Sign up to set email alerts
|

Surveilling Influenza Incidence With Centers for Disease Control and Prevention Web Traffic Data: Demonstration Using a Novel Dataset

Abstract: Background Influenza epidemics result in a public health and economic burden worldwide. Traditional surveillance techniques, which rely on doctor visits, provide data with a delay of 1 to 2 weeks. A means of obtaining real-time data and forecasting future outbreaks is desirable to provide more timely responses to influenza epidemics. Objective Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Our search identified 10 articles addressing internet search queries or webpage views. 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 Four articles studied Baidu, a popular internet search engine in China. 38 , 39 , 41 , 44 Three of these provided data on both correlative value and timeliness.…”
Section: Resultsmentioning
confidence: 99%
“…Our search identified 10 articles addressing internet search queries or webpage views. 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 Four articles studied Baidu, a popular internet search engine in China. 38 , 39 , 41 , 44 Three of these provided data on both correlative value and timeliness.…”
Section: Resultsmentioning
confidence: 99%
“…This inclusive approach is central to achieving a comprehensive and equitable development of healthcare resources, aligning with the objectives of your study. [16–18]…”
Section: Discussionmentioning
confidence: 99%
“…PHI is an imperfect source of data with its own biases such that its content and frequency of posting are not equally distributed across the population. For example, a recent secondary analysis of survey data revealed that women were more likely to post on COVID-19 than men; that black, Latino, and other non-white males were more likely to post on the topic than whites, and that people age 65 and above were more likely to post than younger people [ 68 ]. However, existing analysis tools take this into account, and use the frequency of posting as a variable in and of itself.…”
Section: Discussionmentioning
confidence: 99%
“…Spearman ( [11,18,31,33,39,54]) Pearson ( [19,20,37,38,43,44,48,49,55,60]) unspecified ( [12,22,25,30,50,51,61]) FDR [23], DBNM [24], KLD [47], JI [51], GCt [53], DFt [53], ARIMAX [55], ESA [57] unspecified ([13,14,30,35,38,43,49,50,61,62]) SARIMA [17], SDA [17], LiR [17], BCP [28], SH-ESD [42], STL [54] unspecified [48] SVM ([15,16,27,35,36,38,44,49,53]) LR ( [35,46,55]) NB ( [36,42] tributed across the population. For example, a recent secondary analysis of survey data revealed that women were more likely to post on COVID-19 than men; that black, Latino, and other non-white males were more likely to post on the topic than whites, and that people age 65 and above were more likely to post than younger people [68]. However, existing analysis tools take this into account, and ...…”
Section: Algorithm or Technique (References Using This Technique)mentioning
confidence: 99%